Efficient synthesis of polyether polyols in simple microreactors. Issue 4 (10th February 2021) - Shu, Jiahui; Yu, Liang; Ding, Rong; Zhang, Lixiong
Abstract : High-quality polyether polyols with different molecular weights were efficiently synthesized in simple microreactors. Abstract : Polyether polyols as a crucial chemical for the synthesis of polyurethanes have attracted much attention, especially for propylene oxide-based polyether polyols due to their ready availability and good structural diversity. In the present work, microreactors configured with a SIMM-V2 micromixer and stainless steel capillary were developed for the continuous and efficient synthesis of propylene oxide-based polyether polyols. For the conversion of propylene oxide higher than 95%, the reaction time was less than 60 s that was significantly shorter than that in a batch reactor. Also, the reaction temperature can be controlled precisely, thereby obtaining high purity polyether polyol products. To identify the maximum performance of the microreactors, while keeping the conversion of PO higher than 95%, the novel process windows of the reactors were determined by investigating the relations of reaction temperature and pressure, reaction temperature and residence time, and feed flow rate and residence time. The results showed that high quality polyether polyols could be easily prepared in the microreactors under flexible operating conditions. In addition, polyether polyols with higher molecular weights could also be prepared by using a two SIMM-V2 configured microreactor. This work showed that the microreactors are promising candidates for the synthesis of polyether polyols in the industry.